Determination of nitrate reductase activity, TNC and hormonal contents in longan leaf after potassium chlorate applications - D. Naphrom (2018)
The experiment was carried out at the Department of Plant Science and Natural Resources Faculty of Agriculture Chiang Mai University, Thailand in late October, 2008. A randomized complete design with 4 replications and 3 treatments was performed. The treatments were control, 12 g/tree KClO3 by soil drenching and 1,000 ppm KClO3 by foliar spraying. Five-year-old potted longan trees cv. Daw were used in this experiment. Leaf samples were collected every 2 days after treatments until flowering. Nitrate reductase activity (NRA), total nonstructural carbohydrate (TNC), total nitrogen (TN), and endogenous hormones were investigated. Radioimmunoassay technique was used for hormone determination. The results revealed that the longan trees were flowering within 3 weeks after KClO3 treatments. Application to the soil gave a higher percentage of flowering of 90%, than foliar spraying treatment, 50%. The NRA and TNC contents in leaves tended to decrease in all treatments, particularly after KClO3 application by soil drenching which showed the lowest NRA and TNC content. On the other hand TN contents were not different in all treatments. Changes in cytokinins concentrations in both forms of iP/iPA and Z/ZR were likely enhanced until prior to flowering in both potassium chlorate treatments as compared to the control. Furthermore, IAA in leaves increased after foliar spraying treatment. Nevertheless, the changes in GA3 had no significant difference in all treatments.